Subsidies for wages and infrastructure: how to restrain undesired immigration - Robert Fenge; Volker Meier (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper investigates regional or international transfers as a means to prevent immigration into unemployment. We analyze a two-country model with free migration in which the rich country is characterized by minimum wage unemployment. Matching grants for investment in infrastructure are superior to wage subsidies because the former instrument leads to a stronger productivity growth in the poor country, reducing both migration flows and unemployment in the rich country. This result is shown to hold for a sufficiently low level of the regional policy budget. It explains the exclusive use of investment subsidies in the EU.
Keywords: D62; H23; H54; H77; J61; R50; 330; Internationale Arbeitsmobilität; Arbeitslosigkeit; Arbeitsmarktpolitik; Arbeitslosenversicherung; Lohnsubvention; Theorie; Public Choice; EU-Staaten